All-solid-state battery
Patent Information
- Application Number
- CN202580022661.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0045]本发明的全固态电池对于通过压缩输入施加的压缩应力,能够抑制正极端部的损伤,并且对于充放电导致的负极的膨胀收缩,能够抑制应力集中于电极层叠体的层叠方向的端部,从而抑制电池反应的局部化导致的锂金属的异常析出、全固态电池的容量下降。
Smart Images

Figure CN122996534A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an all-solid-state battery. Background Technology
[0002] In recent years, in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy, research and development are underway on rechargeable batteries that can help improve energy efficiency. As a rechargeable battery, high-energy-density lithium metal batteries have attracted considerable attention.
[0003] Lithium metal batteries are secondary batteries that use lithium metal as the negative electrode and can be high-capacity batteries. Among them, all-solid-state lithium metal batteries, which replace the electrolyte with a solid electrolyte layer to achieve a fully solid state, have attracted much attention due to their excellent safety. All-solid-state lithium metal batteries, for example, have the following battery structure: a negative electrode, a positive electrode, and a solid electrolyte layer made of lithium metal (Patent Document 1, Patent Document 2).
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Publication No. 6863299
[0007] Patent Document 2: International Publication No. 2023 / 188741 Summary of the Invention
[0008] The technical problem that the invention aims to solve
[0009] However, if an extended resin coating is provided at the ends of the electrode stack in the stacking direction, stress concentration will occur due to the expansion and contraction of the negative electrode caused by the charging and discharging of the all-solid-state battery, especially at the positive electrode and the solid electrolyte layer located at both ends of the electrode stack in the stacking direction.
[0010] Furthermore, through repeated charge-discharge cycles of the all-solid-state battery, the positive electrode and solid electrolyte layer at both ends of the electrode stack in the stacking direction are repeatedly subjected to stress concentration. As a result, for example, if damage such as cracks occurs in the solid electrolyte layer at the ends of the electrode stack in the stacking direction, abnormal lithium metal deposition will occur due to the localization of the battery reaction. In addition, if damage such as cracks occurs in the positive electrode active material layer (positive electrode layer) at the ends of the electrode stack in the stacking direction, the capacity of the all-solid-state battery will decrease.
[0011] The present invention was made in view of the above circumstances, and its object is to provide an all-solid-state battery that can suppress damage to the positive terminal portion under compressive stress applied by compression input, and can suppress stress concentration at the end of the electrode stack in the stacking direction of the negative electrode due to expansion and contraction caused by charging and discharging of the all-solid-state battery, thereby suppressing abnormal lithium metal deposition and capacity reduction of the all-solid-state battery caused by localization of battery reaction.
[0012] Technical solutions for solving technical problems
[0013] The inventors conducted repeated and in-depth research to achieve the above-mentioned objectives. They then discovered that if the resin coating is provided at approximately the center of the electrode stack in the stacking direction, instead of at both ends of the electrode stack, the above-mentioned technical problem can be solved, thereby completing the present invention.
[0014] That is, the present invention includes the following methods.
[0015] [1] An all-solid-state battery includes an electrode body consisting of a positive current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative current collector stacked sequentially, and comprises an electrode stack consisting of multiple said electrode bodies stacked together, wherein,
[0016] The surface of the positive current collector on the positive electrode layer side has an insulating material adjacent to the end of the positive electrode layer.
[0017] The solid electrolyte layer is disposed in contact with the positive electrode layer and the insulating material.
[0018] In a direction perpendicular to the stacking direction of the electrode stack, the end of the insulating material is located further outward than the end of the negative electrode layer and the end of the negative electrode current collector.
[0019] In the stacking direction of the electrode laminate, a resin coating is disposed at the end of the electrode laminate in such a way that it abuts against the end of the insulating material.
[0020] It has a laminated film covering the electrode stack.
[0021] The resin coating is disposed at least in the portion corresponding to the sealing portion of the laminated film.
[0022] [2] The all-solid-state battery according to method [1], wherein,
[0023] The resin coating is such that the length of the portion of the electrode laminate that abuts against the end of the insulating material in the lamination direction is more than 1 / 6 of the length of the electrode laminate in the lamination direction and less than the total length.
[0024] [3] The all-solid-state battery according to method [1], wherein,
[0025] The Young's modulus of the resin coating is above 0.1 MPa and below 500 MPa.
[0026] [4] The all-solid-state battery according to method [3], wherein,
[0027] The resin coating is made of a material whose Young's modulus decreases as the temperature rises from -40°C to 100°C, and has a Young's modulus at 25°C that is above 0.1 MPa and below 40 MPa.
[0028] [5] The all-solid-state battery according to method [3], wherein,
[0029] The limiting strain of the solid electrolyte layer is above 0.05% and below 1.00%.
[0030] The Young's modulus of the resin coating is above 0.1 MPa and below 5.0 MPa.
[0031] [6] The all-solid-state battery according to method [1] is characterized in that,
[0032] The laminated film includes a receiving portion for housing the electrode stack and a peripheral portion surrounding the receiving portion.
[0033] The sealing part is disposed on the peripheral portion.
[0034] The sealing portion is located approximately at the center of the electrode stack in the stacking direction.
[0035] [7] The all-solid-state battery according to method [6] is characterized in that,
[0036] The sealing part has a fold-back section.
[0037] It has a first region and a second region, among which,
[0038] The first region extends to one side of the stacking direction of the electrode stack;
[0039] The second region extends from one end of the first region to the opposite side.
[0040] [8] The all-solid-state battery according to method [7] is characterized in that,
[0041] It has a third region that extends from the end of the second region on the other side toward the folded portion.
[0042] [9] The all-solid-state battery according to method [1] or [2], wherein,
[0043] The laminated film is configured to have excess length at both ends in the stacking direction of the electrode stack.
[0044] Invention Effects
[0045] The all-solid-state battery of the present invention can suppress damage to the positive terminal end to the compressive stress applied by the compression input, and can suppress stress concentration at the end of the electrode stack in the stacking direction to the expansion and contraction of the negative electrode caused by charging and discharging, thereby suppressing abnormal lithium metal deposition and capacity reduction of the all-solid-state battery caused by localization of battery reaction. Attached Figure Description
[0046] Figure 1A This is a cross-sectional view showing the structure of the all-solid-state battery under full discharge according to the first embodiment of the present invention.
[0047] Figure 1B This is a cross-sectional view showing the structure of the all-solid-state battery according to the first embodiment of the present invention when fully charged.
[0048] Figure 2A This is a cross-sectional view showing the structure of the all-solid-state battery under full discharge according to the second embodiment of the present invention.
[0049] Figure 2B This is a cross-sectional view showing the structure of the all-solid-state battery according to the second embodiment of the present invention when fully charged.
[0050] Figure 3 This is a partial cross-sectional view showing an example of the configuration of the laminated film on the all-solid-state battery according to the first embodiment.
[0051] Figure 4 This is a partial cross-sectional view showing an example of the configuration of the laminated film on the all-solid-state battery according to the third embodiment.
[0052] Figure 5 This is an enlarged cross-sectional view showing the structure of the electrode stack used in the all-solid-state battery according to the first and second embodiments. Detailed Implementation
[0053] <All-solid-state batteries>
[0054] The all-solid-state battery of the present invention includes an electrode body consisting of a positive current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative current collector stacked sequentially, and comprises an electrode stack consisting of multiple electrode bodies stacked together. The surface of the positive current collector on the positive electrode layer side has an insulating material adjacent to the end of the positive electrode layer, and the solid electrolyte layer is disposed in contact with the positive electrode layer and the insulating material.
[0055] In the all-solid-state battery of the present invention, in a direction perpendicular to the stacking direction of the electrode stack, the end of the insulating material is located outside the end of the negative electrode layer and the end of the negative electrode current collector. In a direction perpendicular to the stacking direction of the electrode stack, a resin coating is disposed at the end of the electrode stack in such a way as to abut against the end of the insulating material, and a laminated film covering the electrode stack is provided.
[0056] Furthermore, in the all-solid-state battery of the present invention, the resin coating is not necessarily disposed at both ends of the electrode laminate in the lamination direction, but is disposed at least in the portion corresponding to the sealing portion of the laminated film. Here, the sealing portion refers to the portion formed by bonding the materials of the outer casing, such as the laminated film, together when the all-solid-state battery is sealed from its outer periphery by the outer casing, for example, by bonding or welding. In addition, the sealing portion can be configured to have a folded-back portion, including a first region and a second region, wherein the first region extends toward one side in the lamination direction of the electrode laminate; and the second region extends from one end of the first region toward the opposite side. Furthermore, the outer casing can be configured such that a first portion, closer to the folded-back portion side than the side of the receiving portion that houses the electrode laminate, includes a first region and a second region, wherein the first region extends from the connection portion with the receiving portion toward one side in the thickness direction of the electrode laminate; and the second region extends from one end of the first region toward the opposite side. In this case, the first part described above can include a third region, which extends from the end of the second region on the other side toward the folded-back portion. Furthermore, the first and third regions described above can be located on the electrode stack side closer to the second region than the second region (for example, see Patent Document 2).
[0057] In one embodiment, the Young's modulus of the resin coating is 0.1 MPa or higher and 500 MPa or lower. In another embodiment, the resin coating is made of a material whose Young's modulus decreases as the temperature rises from -40°C to 100°C, and its Young's modulus at 25°C is 0.1 MPa or higher and 40 MPa or lower. Based on this characteristic of the resin coating, the all-solid-state battery of the present invention can suppress damage to the positive terminal portion under compressive stress applied by compression input, and can suppress stress concentration at the ends of the electrode stack in the stacking direction of the electrode stack due to expansion and contraction of the negative electrode caused by charging and discharging, thereby suppressing abnormal lithium metal deposition and capacity reduction of the all-solid-state battery caused by localization of the battery reaction. In one embodiment, the limiting strain of the solid electrolyte layer of the solid-state battery is 0.05% or higher and 1.00% or lower, and the Young's modulus of the resin coating is 0.1 MPa or higher and 5.0 MPa or lower.
[0058] <First Embodiment>
[0059] Figure 1A and Figure 1BThis is a cross-sectional view showing the structure of the all-solid-state battery according to the first embodiment. Figure 1A This is a diagram showing the state of the all-solid-state battery according to the first embodiment when fully discharged (SOC: 0%). Figure 1B This is a diagram showing the state of the all-solid-state battery according to the first embodiment when fully charged (SOC: 100%).
[0060] Figure 1A and Figure 1B The electrode stack 1 of the all-solid-state battery shown includes: a negative electrode formed by a negative current collector 2a and a lithium metal layer (negative electrode layer) 3a, or a negative current collector 2b and a lithium metal layer (magnetic pole layer) 3b; a positive electrode formed by a positive current collector 4 and a positive active material layer (positive electrode layer) 5a or 5b; and solid electrolyte layers 6a and 6b adjacent to the positive active material layer (positive electrode layer) 5a or 5b.
[0061] Figure 1A and Figure 1B The electrode stack 1 of the all-solid-state battery shown has an intermediate layer 7a between the lithium metal layer (negative electrode layer) 3a and the solid electrolyte layer 6a, and an intermediate layer 7b between the lithium metal layer (negative electrode layer) 3b and the solid electrolyte layer 6b. Furthermore, insulating material 8a is disposed at both ends of the positive electrode active material layer (positive electrode layer) 5a, and insulating material 8b is disposed at both ends of the positive electrode active material layer (positive electrode layer) 5b. In the figure, L represents the direction perpendicular to the stacking direction (surface direction) of the electrode stack 1 constituting the all-solid-state battery.
[0062] In the all-solid-state battery according to the first embodiment, in a direction perpendicular to the stacking direction of the electrode stack 1, the ends of the insulating materials 8a and 8b are located on the outer side of the ends of the lithium metal layer (negative electrode layer) 3a and 3b and the ends of the negative electrode current collectors 2a and 2b.
[0063] In the all-solid-state battery according to the first embodiment, a resin coating 9 is disposed at the end of the electrode stack 1 in a direction perpendicular to the stacking direction of the electrode stack 1, in such a way that it abuts against the ends of the insulating materials 8a and 8b.
[0064] In the all-solid-state battery according to the first embodiment, the resin coating 9 is not necessarily disposed at both ends of the electrode laminate 1 in the lamination direction, but is disposed at least at the portion corresponding to the sealing portion of the laminated film. Here, in order to improve battery durability, the sealing of the laminated film needs to cover the entire electrode laminate 1 and be performed under vacuum. In this vacuum sealing process, the compressive stress generated by the vacuum is input from the outside of the sealing portion of the laminated film toward the interior of the electrode laminate 1 in a direction perpendicular to the lamination direction of the electrode laminate 1. By distributing the end coating at least at this sealing portion, it is possible to prevent the compressive input from this sealing portion to the interior of the electrode laminate 1 from being concentrated at one end of the insulating materials 8a, 8b, thereby distributing the stress to more than one end.
[0065] like Figure 1A As shown, in a fully discharged (SOC: 0%) solid-state battery, the lithium metal layers (negative electrode layers) 3a, 3b, etc. are in an unexpanded state, and the resin coating 9 disposed at approximately the center of the electrode stack 1 in the stacking direction exists in a state that does not cause deformation of the electrode stack.
[0066] like Figure 1B As shown, in a fully charged (SOC: 100%) all-solid-state battery, due to the expansion of the lithium metal layers (negative electrode layers) 3a, 3b, etc., the thickness (length Hb in the stacking direction) of the electrode stack 1 is greater than that of the battery. Figure 1A The electrode stack 1 shown has a large thickness (length Ha in the stacking direction) when fully discharged (SOC: 0%).
[0067] At this time, since the resin coating 9 of the all-solid-state battery according to the first embodiment is not disposed at both ends of the electrode stack 1 where the amount of variation is large, but is disposed approximately at the center of the electrode stack 1 where the amount of variation is small, the deformation caused by the stretching of the structural portions extending outward from the ends of the electrode stack 1, namely the positive electrode and the solid electrolyte layer, by the resin coating 9 is small. In addition, since the resin coating 9 is not disposed at both ends of the electrode stack 1 in the stacking direction, the positive electrode active material layer (positive electrode layer) and the solid electrolyte layer located at both ends of the electrode stack 1 in the stacking direction are not stretched by the resin coating 9.
[0068] As a result, the all-solid-state battery according to the first embodiment can suppress damage to the positive terminal due to the presence of the resin coating, and can avoid stress concentration on the positive active material layer (positive electrode layer) and the solid electrolyte layer located at both ends of the electrode stack in the stacking direction of the electrode stack, even if the lithium metal layer (negative electrode layer) expands during charging.
[0069] <Second Implementation>
[0070] Figure 2A and Figure 2B This is a cross-sectional view showing the structure of the all-solid-state battery according to the second embodiment. Figure 2A This is a diagram showing the state of the all-solid-state battery according to the first embodiment when fully discharged (SOC: 0%). Figure 2B (b) A diagram showing the state of the all-solid-state battery according to the second embodiment when fully charged (SOC: 100%).
[0071] In the all-solid-state battery according to the second embodiment, it is the same as the first embodiment, except that the resin coating 9a is set to cover the entire electrode stack 1 including both ends of the electrode stack 1 in the stacking direction, and the Young's modulus of the resin coating 9a at 25°C is 0.1 MPa or more and 500 MPa or less. Therefore, the same reference numerals are used to refer to the same structure as the all-solid-state battery according to the first embodiment, and detailed descriptions are omitted.
[0072] like Figure 2A As shown, in the all-solid-state battery at full discharge (SOC: 0%), the resin coating 9a is configured to cover the entire electrode stack 1 in a non-stretched state. Therefore, the thickness of the electrode stack 1 (length Ha in the stacking direction) and the thickness of the resin coating 9a (length T1 in the stacking direction) are the same.
[0073] like Figure 2B As shown, in a fully charged (SOC: 100%) all-solid-state battery, the resin coating 9a elongates as the thickness (length Hb in the stacking direction) of the electrode stack 1 increases, and is configured to cover the entire electrode stack 1. Therefore, the thickness (length Hb in the stacking direction) of the electrode stack 1 and the thickness (length T2 in the stacking direction) of the resin coating 9a are the same.
[0074] The resin coating 9 of the all-solid-state battery according to the second embodiment is such that, since the thickness of the electrode stack 1 elongates according to the change in the thickness of the electrode stack 1, the deformation caused by the stretching of the positive electrode and solid electrolyte layers by the resin coating 9 is small. As a result, the all-solid-state battery according to the second embodiment, by virtue of the presence of the resin coating 9a, can suppress damage to the positive terminal end to the compressive stress applied by the compressive input, and even if the lithium metal layer (negative electrode layer) expands during charging, stress concentration can be avoided at the positive electrode active material layer (positive electrode layer) and the solid electrolyte layer located at both ends of the electrode stack in the stacking direction.
[0075] In order for the resin coating 9a to elongate according to the change in thickness of the electrode laminate 1, the Young's modulus of the resin coating 9a at 25°C is preferably 0.1 MPa or more and 40 MPa or less. In addition, the resin coating 9 is preferably made of a material whose Young's modulus decreases as the temperature rises from -40°C to 100°C.
[0076] <Third Implementation>
[0077] The third embodiment involves Figure 3 This is a partial cross-sectional view showing an example of the configuration of the laminated thin film on the all-solid-state battery according to the first embodiment. The structure of the electrode stack 1 of the all-solid-state battery according to the third embodiment is the same as the structure of the electrode stack 1 of the all-solid-state battery according to the first embodiment described above.
[0078] In the all-solid-state battery according to the third embodiment, the electrode stack 1 and the resin coating 9 of the first embodiment are covered by the laminated film 10. Figure 3 This is a partial cross-sectional view near the end of the electrode laminate 1 in the lamination direction. Here, the resin coating 9 is not necessarily disposed at both ends of the electrode laminate 1 in the lamination direction, but is disposed at least in the portion corresponding to the sealing portion of the laminated film 10. Furthermore, the laminated film 10 includes a receiving portion 101 that houses the electrode laminate 1, and a peripheral portion surrounding the receiving portion 101. The aforementioned sealing portion 102 is disposed in this peripheral portion, and the sealing portion 102 is disposed approximately at the center of the electrode laminate 1 in the lamination direction.
[0079] exist Figure 3 In the all-solid-state battery according to the third embodiment shown, the laminated films 10 at both ends of the electrode stack 1 in the stacking direction are arranged with a margin of excess length. By having a margin of excess length for the laminated films 10 at both ends of the electrode stack 1 in the stacking direction, even if the thickness of the electrode stack (length in the stacking direction H) increases due to the expansion of the lithium metal layer (negative electrode layer) when the all-solid-state battery is fully charged (SOC: 100%), the positive electrode active material layer (positive electrode layer) and the solid electrolyte layer at both ends of the electrode stack in the stacking direction can be prevented from being stretched by the laminated films.
[0080] Therefore, in addition to the resin coating configuration of the first embodiment, by adopting the laminated film state of the third embodiment, even if the lithium metal layer (negative electrode layer) expands during charging, stress concentration on the positive electrode active material layer (positive electrode layer) and the solid electrolyte layer located at both ends of the stacking direction of the electrode laminate can be avoided to a high degree.
[0081] <Fourth Implementation>
[0082] In the all-solid-state battery according to the fourth embodiment, the electrode stack 1 and the resin coating 9a of the second embodiment are covered by a laminated film 10. The sealing portion 102 of the laminated film 10 is bent at the bending portion 11 along the lamination direction, and has one side facing the lamination direction of the electrode stack ( Figure 4 The first region 111 extends from the lower center and the folded portion from one end of the first region 111 to the opposite side. Figure 4 The second region 112, extending from the upper middle part, is otherwise identical to that in the first embodiment. Therefore, the same reference numerals are used to refer to the same structure as that of the all-solid-state battery in the first embodiment, and detailed descriptions are omitted.
[0083] In the all-solid-state battery according to the fourth embodiment, similar to the all-solid-state battery according to the third embodiment, the laminated films 10 located at both ends of the electrode laminate 1 in the lamination direction are arranged with a sufficient length. Therefore, even if the lithium metal layer (negative electrode layer) expands during charging, stress concentration at both ends of the electrode laminate in the lamination direction can be avoided to a high degree. Furthermore, in the all-solid-state battery according to the fourth embodiment, since the sealing portion 102 is relatively long, the sealing portion 102 is less prone to cracking. Also, it is possible to provide a sealing portion from the other side of the second region (… Figure 4 The end of the middle and upper part is directed to one side ( Figure 4 The third region extends from the lower middle side to the folding section.
[0084] <Structure of all-solid-state batteries>
[0085] The structures of the all-solid-state battery of the present invention will now be described. Figure 5 This is an enlarged cross-sectional view of the electrode stack used in the all-solid-state batteries of the first and second embodiments.
[0086] [Positive current collector 4]
[0087] The positive electrode current collector used in the all-solid-state battery of the present invention is configured to contact the positive electrode layer, thus enabling current collection from the positive electrode layer. The material used as the positive electrode current collector is not particularly limited, as long as it can perform current collection from the positive electrode layer. Examples of materials used as the positive electrode current collector include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium, among which at least one selected from the group consisting of aluminum, aluminum alloys, and stainless steel is preferred.
[0088] The shape of the positive electrode current collector is not particularly limited; for example, it can be foil-shaped or plate-shaped. Furthermore, the thickness of the positive electrode current collector is not particularly limited and can be the same as that used in typical all-solid-state batteries. The thickness of the positive electrode current collector is, for example, in the range of 0.1 μm or more and 1 mm or less.
[0089] [Positive electrode layers 5a, 5b]
[0090] The positive electrode layer is a layer containing at least a positive electrode active material. There are no particular limitations on the positive electrode active material contained in the positive electrode layer; any material used in the positive electrode layer of a typical all-solid-state battery is acceptable. Examples of positive electrode active materials, for example, in lithium-ion batteries, include layered active materials containing lithium, spinel-type active materials, and olivine-type active materials. Specific examples of positive electrode active materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and LiNi... p Mn q Co r O2 (p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese oxide (LiMn2O4), Li 1+x Mn 2-x-y MyO4 (x+y=2, M is at least one selected from Al, Mg, Co, Fe, Ni and Zn) represents heteroelement-substituted Li-Mn spinel, lithium titanate (an oxide containing Li and Ti), lithium metal phosphate (LiMPO4, M is at least one selected from Fe, Mn, Co and Ni), etc.
[0091] The content of the positive electrode active material in the positive electrode layer is, for example, in the range of 50% to 99% by mass. The surface of the positive electrode active material can also be covered by oxide layers such as lithium niobate, lithium titanate, and lithium phosphate.
[0092] To improve lithium-ion conductivity, the positive electrode layer can arbitrarily contain the solid electrolyte described later. Furthermore, the positive electrode layer can arbitrarily contain binders, conductive additives, etc. Materials commonly used in all-solid-state batteries can be used as these materials.
[0093] The thickness of the positive electrode layer is not particularly limited and can be appropriately set according to the required battery performance. For example, the thickness of the positive electrode layer can be in the range of 0.1 μm or more and 1 mm or less.
[0094] In the case of the all-solid-state battery of the present invention having the intermediate layer described later, the positive electrode layer preferably has an area equal to that of the intermediate layer on the laminated surface. This improves the energy density of the all-solid-state battery. The area of the positive electrode layer in the all-solid-state battery of the present invention can, for example, be up to 100% of the area of the intermediate layer, or it can be 90% to 100% of the area of the intermediate layer, or it can be 80% to 90%.
[0095] There is no particular limitation on the manufacturing method of the positive electrode layer, and it can be manufactured by known methods. For example, the material constituting the positive electrode layer can be mixed with a solvent to form a slurry, and the slurry can be coated on the aforementioned positive electrode current collector and then dried to manufacture the positive electrode layer.
[0096] [Solid electrolyte layers 6a, 6b]
[0097] The solid electrolyte layer is a layer that includes a solid electrolyte. The solid electrolyte layer is disposed in contact with the positive electrode layer and the insulating material.
[0098] There are no particular limitations on the materials used for solid-state electrolytes, as long as they possess lithium-ion conductivity and insulation properties. Materials commonly used in all-solid-state lithium-ion batteries can be used as solid-state electrolyte materials, such as sulfide solid-state electrolyte materials, oxide solid-state electrolyte materials, halide solid-state electrolytes, inorganic solid-state electrolytes containing lithium salts, polymeric solid-state electrolytes such as polyethylene oxide, and gel-based solid-state electrolytes containing lithium salts and lithium-ion conductive ionic liquids. Among these, sulfide solid-state electrolyte materials are preferred from the viewpoints of high lithium-ion conductivity and good structural formability and interfacial bonding formed under pressure.
[0099] The form of the solid electrolyte material is not particularly limited; for example, it can be granular. Furthermore, the content of the solid electrolyte in the solid electrolyte layer of the all-solid-state battery of the present invention is not particularly limited. The content of the solid electrolyte can, for example, be in the range of 50% to 99% by mass.
[0100] The solid electrolyte layer can contain binders arbitrarily. Additionally, adhesives can be included arbitrarily for the purpose of imparting mechanical strength and flexibility. Materials commonly used in all-solid-state batteries can be used as these materials.
[0101] The solid electrolyte layer can also be configured such that, in a direction perpendicular to the stacking direction of the electrode stack of the all-solid-state battery of the present invention, the end is located at approximately the same position as the end of the insulating material.
[0102] Since this type of electrode stack does not have a solid electrolyte layer protruding from the end face of the electrode stack, for example, when pressure such as rolling is applied during the manufacturing process of the electrode stack, cracks in the solid electrolyte layer can be suppressed.
[0103] There is no particular limitation on the manufacturing method of the solid electrolyte layer; it can be manufactured by known methods. For example, the materials constituting the solid electrolyte layer can be mixed with a solvent to form a slurry, the slurry can be coated onto a substrate, and then dried to manufacture the solid electrolyte layer.
[0104] [Negative electrode current collectors 2a, 2b]
[0105] The negative electrode current collector used in the all-solid-state battery of the present invention is configured to contact the negative electrode layer, thus enabling current collection from the negative electrode layer. The material used as the negative electrode current collector is not particularly limited, as long as it can collect current from the negative electrode layer; however, it is preferably composed of a material with high conductivity. Examples of materials with high conductivity include: metals containing at least one metallic element selected from the group consisting of silver, palladium, gold, platinum, aluminum, copper, and nickel; alloys such as stainless steel; and non-metals such as carbon (C).
[0106] Among these highly conductive materials, when manufacturing costs are considered in addition to conductivity, at least one material selected from the group consisting of copper, stainless steel, and nickel is preferred. In particular, since stainless steel is difficult to react with the negative electrode active material, the positive electrode active material, and the solid electrolyte, using stainless steel as the negative electrode current collector material can reduce the internal resistance of the all-solid-state battery.
[0107] There are no particular limitations on the shape of the negative electrode current collector; for example, it can be foil-shaped, plate-shaped, mesh-shaped, non-woven fabric-shaped, foam-shaped, etc. In addition, in order to improve the adhesion with the negative electrode layer, a carbon layer can be deposited on the surface of the negative electrode current collector, or the surface can be roughened.
[0108] The thickness of the negative electrode current collector is not particularly limited and can be the same as that used in the negative electrode of a typical all-solid-state battery. The thickness of the negative electrode current collector can, for example, be in the range of 0.1 μm or more and 1 mm or less.
[0109] [Negative electrode layers 3a, 3b]
[0110] The negative electrode layer is a layer containing a negative electrode active material that accepts and absorbs lithium ions and electrons. There are no particular limitations on the negative electrode active material contained in the negative electrode layer; any negative electrode active material commonly used in all-solid-state batteries can be used. However, materials with high electron conductivity are preferred to enable reversible release, absorption, and encapsulation of lithium ions and facilitate electron transport. Examples of such negative electrode active materials include silicon-based active materials such as silicon and silicon alloys, carbon-based active materials such as graphite and hard carbon, various oxide-based active materials such as lithium titanate, and lithium-based active materials such as metallic lithium and lithium alloys. One of the above-mentioned materials can be used alone, or two or more can be used in combination.
[0111] In the all-solid-state battery of the present invention, the negative electrode layer can be a layer composed of lithium metal or a lithium metal alloy alone or in combination. Since the negative electrode layer composed of lithium metal or a lithium metal alloy alone or in combination has a large capacity per unit weight, a high-capacity all-solid-state battery can be realized.
[0112] The content of the negative electrode active material in the negative electrode layer can be, for example, in the range of 30% to 100% by mass.
[0113] To improve lithium-ion conductivity, the negative electrode layer can contain any of the aforementioned solid electrolytes. Additionally, the negative electrode layer can contain binders, conductive additives, etc. These materials can be those commonly used in all-solid-state batteries.
[0114] There is no particular limitation on the thickness of the negative electrode layer; it can be appropriately set according to the required battery performance. For example, the thickness of the negative electrode layer can be in the range of 0.1 μm to 1 mm.
[0115] There is no particular limitation on the manufacturing method of the negative electrode layer, and it can be manufactured by known methods. For example, the material constituting the negative electrode layer can be mixed with a solvent to form a slurry, and the slurry can be coated on the aforementioned negative electrode current collector and then dried to manufacture the negative electrode layer.
[0116] [Intermediate layers 7a, 7b]
[0117] In the case of the all-solid-state battery of the present invention having an intermediate layer, an intermediate layer is provided between the solid electrolyte and the negative electrode layer. When the negative electrode layer of the all-solid-state battery of the present invention is a layer composed of metallic lithium or a lithium metal alloy alone or in combination, by providing an intermediate layer between the solid electrolyte layer and the negative electrode layer, it is possible to suppress the uneven precipitation of dendrites at the interface between the solid electrolyte layer and the negative electrode layer, and to improve the interface adhesion.
[0118] The intermediate layer is a layer that has both electronic and ionic conductivity. Because the intermediate layer has ionic conductivity, it allows lithium ions to pass through, for example. Therefore, with repeated charge and discharge cycles of the all-solid-state battery, lithium ions (Li) migrate from the solid electrolyte layer to the negative electrode layer. + The intermediate layer allows for uniform lithium metal deposition between the intermediate layer and the negative electrode layer. Furthermore, the flexibility of the intermediate layer ensures that the interface adhesion remains intact even after repeated charge-discharge cycles, thus improving the durability of the all-solid-state battery. Flexibility refers to the intermediate layer's ability to adapt to volume changes caused by charge-discharge cycles.
[0119] In a direction perpendicular to the stacking direction of the electrode stack of the all-solid-state battery of the present invention, the end of the intermediate layer can be disposed at approximately the same position as the end of the negative electrode layer, or it can be disposed at a position further inward than the end of the negative electrode layer. Accordingly, the effect of disposing of the intermediate layer as described above can be fully realized.
[0120] There are no particular limitations on the materials used to form the intermediate layer. For example, the intermediate layer may contain amorphous carbon, metal nanoparticles, and a binder as a bonding material.
[0121] Unlike graphite, amorphous carbon does not react with lithium metal to alloy. Therefore, it can suppress dendrite formation and improve the cycle characteristics of all-solid-state batteries.
[0122] Examples of amorphous carbon include acetylene black, furnace black, Ketjen black, coke, and activated carbon. Amorphous carbon can be easily graphitized carbon (soft carbon), or difficult-to-graphitize carbon (hard carbon), CNTs (carbon nanotubes), fullerenes, and graphene.
[0123] Because the intermediate layer contains metal nanoparticles, its electronic conductivity is improved, resulting in more uniform lithium metal deposition. There are no particular limitations on the metal nanoparticles used; examples include tin, silicon, zinc, magnesium, gold, platinum, palladium, silver, aluminum, bismuth, and antimony nanoparticles.
[0124] The binder contained in the intermediate layer maintains the structure of the intermediate layer and improves the adhesion between the particles constituting the intermediate layer and between the intermediate layer and the solid electrolyte layer. There are no particular limitations on the binder; binders commonly used in all-solid-state batteries can be used.
[0125] [Insulating materials 8a, 8b]
[0126] An insulating material is disposed adjacent to the end of the positive electrode layer on the surface of the positive electrode current collector. By disposing of the insulating material at the end of the positive electrode layer, when the tab leads extending from the negative electrode current collectors of each battery structure are gathered to function as a battery, the bending of the tab leads can prevent the tab leads from contacting the positive terminal to suppress short circuits. Furthermore, it can suppress the generation of cracks caused by volume changes due to repeated charging and discharging, and also suppress short circuits caused by cracks.
[0127] The shape of the insulating material is not limited, as long as it is disposed at the end of the positive electrode layer. The size of the insulating material is not particularly limited, as long as it has a thickness less than that of the positive electrode layer in the stacking direction of the electrode stack, and abuts against part or all of the end face of the positive electrode layer, and is disposed at the end of the positive electrode layer in a direction perpendicular to the stacking direction of the electrode stack.
[0128] There are no particular limitations on the materials used as insulating materials, as long as they exhibit insulating properties. They can be any insulator other than semiconductors and conductors. The materials used for insulating materials can be appropriately selected based on the insulating properties that are desired to be added.
[0129] There are no particular limitations on the manufacturing method of insulating materials. For example, they can be manufactured by coating a slurry containing an insulating material onto a positive current collector on which a positive electrode layer has been formed, and then drying it.
[0130] [Resin coatings 9, 9a]
[0131] In the all-solid-state battery of the present invention, the resin coating is disposed at the ends of the electrode stack in the stacking direction of the electrode stack, in a manner abutting against the ends of the insulating material. The resin coating is not disposed at both ends of the electrode stack in the stacking direction, but only at approximately the center of the electrode stack in the stacking direction.
[0132] The resin coating of the all-solid-state battery of the present invention can be provided in a manner that abuts against the end of the insulating material. In a direction perpendicular to the stacking direction of the electrode stack, it can enter the space adjacent to the end of the negative electrode layer and the end of the negative electrode current collector, which is inside the end of the insulating material, or it can not enter this space.
[0133] The resin coating can be applied by chamfering (C-shaped or R-shaped) the corners of the ends that do not contact the insulating material in the stacking direction of the electrode stack. By providing C-shaped or R-shaped chamfers at the corners, uneven contact at the ends can be prevented, and the stability of stacking misalignment during stacking or input can be improved.
[0134] Preferably, the length of the end of the electrode laminate that abuts the end of the insulating material in the lamination direction is at least 1 / 8 of the length of the electrode laminate in the lamination direction. If the length of the resin coating is at least 1 / 8 of the length of the electrode laminate in the lamination direction, damage to the positive terminal can be suppressed at a higher level for compressive stress applied by compression input.
[0135] The resin coating 9 used in the all-solid-state battery of the first embodiment preferably has a length of the end of the electrode stack that abuts against the end of the insulating material in the stacking direction of the electrode stack that is less than half the length of the electrode stack in the stacking direction. If the length of the resin coating is less than half the length of the electrode stack in the stacking direction, the expansion and contraction of the negative electrode caused by the charging and discharging of the all-solid-state battery can be suppressed to a higher level to prevent stress concentration at the end of the electrode stack in the stacking direction, thus suppressing abnormal lithium metal deposition and capacity reduction of the all-solid-state battery caused by localization of the battery reaction. On the other hand, the resin coating 9a used in the all-solid-state battery of the second embodiment may have a length of the end of the electrode stack that abuts against the end of the insulating material in the stacking direction that is the same as the length of the electrode stack in the stacking direction.
[0136] There are no particular limitations on the manufacturing method of the resin coating. For example, known methods can be used, such as applying materials that can be used to coat the ends of insulating materials to form a resin coating.
[0137] Examples of resin coating materials include thermosetting resins and UV-curable resins. If a UV-curable resin is used, acrylic-based (free radical polymerization using unsaturated double bonds) and cationic (cationic polymerization) resins can be selected. Resin coating materials with a hardened Young's modulus of 0.01 MPa or higher and 40 MPa or lower can be selected, and those with a Young's modulus of 0.1 MPa or higher and 5 MPa or lower are preferred.
[0138] <Manufacturing Method of All-Solid-State Batteries>
[0139] The manufacturing method of the all-solid-state battery of the present invention is not particularly limited, and known methods can be used. For example, an electrode body is formed by sequentially stacking a negative electrode current collector, a negative electrode layer, an intermediate layer, a solid electrolyte layer, a positive electrode layer, and a positive electrode current collector, and forming an insulating material on the positive electrode current collector at both ends of the positive electrode layer. Afterward, multiple electrode bodies are stacked, arbitrarily pressurized, and integrated to form an electrode stack. Furthermore, by forming a resin coating at the ends of the electrode stack, the all-solid-state battery of the present invention can be manufactured.
[0140] Subsequently, by using known methods, an electrode stack with a resin coating is encapsulated in a laminated film and sealed using known methods, thereby enabling the final all-solid-state battery to be manufactured.
[0141] The preferred embodiments of the present invention have been described above, but the present invention is not limited to the above embodiments. Any modifications or improvements made within the scope of achieving the purpose of the present invention are included in the present invention.
[0142] Explanation of reference numerals in the attached figures
[0143] 1: Electrode laminate; 2a, 2b: Negative electrode current collector; 3a, 3b: Lithium metal layer (negative electrode layer); 4: Positive electrode current collector; 5a, 5b: Positive electrode active material layer (positive electrode layer); 6a, 6b: Solid electrolyte layer; 7a, 7b: Intermediate layer; 8a, 8b: Insulating material; 9: Resin coating; 10: Laminated film; 11: Bending portion; 101: Receiving portion; 102: Sealing portion; 111: Region 1; 112: Region 2; H, Ha, Hb: Lamination direction of the electrode laminate; L: Direction perpendicular to the lamination direction of the electrode laminate (surface direction); T, T1, T2: Thickness of the resin-coated electrode laminate in the lamination direction.
Claims
1. An all-solid-state battery, comprising an electrode body consisting of a positive current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative current collector stacked sequentially, and further comprising an electrode stack consisting of multiple said electrode bodies stacked together, characterized in that, The surface of the positive current collector on the positive electrode layer side has an insulating material adjacent to the end of the positive electrode layer. The solid electrolyte layer is disposed in contact with the positive electrode layer and the insulating material. In a direction perpendicular to the stacking direction of the electrode stack, the end of the insulating material is located further outward than the end of the negative electrode layer and the end of the negative electrode current collector. In the stacking direction of the electrode laminate, a resin coating is disposed at the end of the electrode laminate in such a way that it abuts against the end of the insulating material. It has a laminated film covering the electrode stack. The resin coating is disposed at least in the portion corresponding to the sealing portion of the laminated film.
2. The all-solid-state battery according to claim 1, characterized in that, In the stacking direction of the electrode laminate, the length of the portion of the resin coating that abuts against the end of the insulating material is more than 1 / 6 of the length of the electrode laminate in the stacking direction and less than the total length.
3. The all-solid-state battery according to claim 1 or 2, characterized in that, The Young's modulus of the resin coating is above 0.1 MPa and below 500 MPa.
4. The all-solid-state battery according to claim 3, characterized in that, The resin coating is made of a material whose Young's modulus decreases as the temperature rises from -40°C to 100°C, and has a Young's modulus at 25°C that is above 0.1 MPa and below 40 MPa.
5. The all-solid-state battery according to claim 3, characterized in that, The limiting strain of the solid electrolyte layer is above 0.05% and below 1.00%. The Young's modulus of the resin coating is above 0.1 MPa and below 5.0 MPa.
6. The all-solid-state battery according to claim 1, characterized in that, The laminated film includes a receiving portion for housing the electrode stack and a peripheral portion surrounding the receiving portion. The sealing part is disposed on the peripheral portion. The sealing portion is located approximately at the center of the electrode stack in the stacking direction.
7. The all-solid-state battery according to claim 6, characterized in that, The sealing part has a fold-back section. It has a first region and a second region, among which, The first region extends to one side of the stacking direction of the electrode stack; The second region extends from one end of the first region to the opposite side.
8. The all-solid-state battery according to claim 7, characterized in that, It has a third region that extends from the end of the second region on the other side toward the folded portion.
9. The all-solid-state battery according to claim 1 or 2, characterized in that, The laminated film is configured to have excess length at both ends in the stacking direction of the electrode stack.
Citation Information
Patent Citations
Storage battery, battery module, and laminated film
WO2023188741A1